Language Literacy Enhancement Through Zoom Cloud Meeting - Azizah Husda; Wanrika Tampubolon; Sara Okta Romindo Sibarani (Universitas PGRI Adi Buana Surabaya, 2022)
This research conducted to analyze the language literacy skills enhancement through zoom cloud meeting. From the research problem, the researchers formulated the purpose of this study was to describe language literacy skills through zoom cloud meetings at Universitas Prima Indonesia in 5th semester and explained the parts of language literacy skills dominantly increased during online learning through zoom cloud meeting in 5th semester students at Universitas Prima Indonesia. This research used qualitative research with the case study method where in data collection using interview by sharing the google form, distributed to 30, 5th semester students at Universitas Prima Indonesia for the Academic Year 2021/2022. The results found that the use of zoom during online learning really helped students in improving their language literacy skills and language literacy skills for Indonesian prima university students when using zoom cloud meetings in online learning, 66.7% and above said it was very good and the literacy section. The dominant language literacy skill enhanced was using zoom cloud meetings is reading ability with a percentage of 53.3%, then followed by listening ability at 26.7%, speaking ability at 16.7%, and writing ability with a percentage of 3.3%